"I'm Not Waving, I'm Drowning": An Autoethnographical Exploration of Biographical Disruption and Reconstruction During Recovery From Prescribed Benzodiazepine Use. (March 2016) - Fixsen, Alison M.
Benzodiazepines are group of drugs used mainly as sedatives, hypnotics, muscle relaxants, and anti-epileptics. Tapering off benzodiazepines is, for some users, a painful, traumatic, and protracted process. In this article, I use an autoethnographic approach, adopting the metaphor of water, to examine heuristically my experience of iatrogenic illness and recovery. I draw on personal journals and blog entries and former users' narratives to consider the particular form of biographical disruption associated with benzodiazepines and the processes involved in identity reconstruction. I emphasize the role of the online community in providing benzodiazepine users such as myself with a co-cultural community through which to share a voice and make sense of our experiences. I explain how the success stories of former users provided me with the hope that I, the "medical victim, " could become the "victor" and in the process construct a new life and fresh identity.